Quasi-Dimensional Multi-Zone Modeling of Methane-Diesel Dual-Fuel Combustion - Xu, Shuonan; Filipi, Zoran (Frontiers in Mechanical Engineering, 2020)
Strict CO2 emission and fuel economy regulations are motivating the developers of internal combustion engines to consider alternative fuels. Dual-fuel NG diesel engines are attractive due to minimal design changes, ability to maintain high compression ratio of the diesel baseline, and elimination of driver’s range anxiety. A typical overarching goal is to maximize the substitution ratio, but the higher complexity of the dual-fuel engine comes with challenges, such as the knock limit at high load, combustion instability at low load and methane slip. Development of dual-fuel engine and its control strategies can benefit from predictive simulations, capable of providing deep insights into combustion and emission formation. They can dramatically lower the time and cost for explorations of design and optimizing engine control strategies. Even when experimental data is available, the simulation can provide useful additional insight by predicting value of parameters that are not easy to measure from experimental setup. This paper presents development of a Quasi-D multi-zone combustion model of a heavy-duty dual-fuel engine. The approach marries the best features of the multi-zonal diesel spray model with the turbulent flame entrainment model for the premixed charge of NG and air/EGR. The diesel combustion model developed in this study is based on the framework proposed by Hiroyasu et al. (Hiroyasu, 1985) with several improvements in its sub-models. Regarding the combustion of the premixed charge, a new way of modeling the flame front area during NG flame propagation is proposed. The NG flame is assumed to initiate from the outer boundary of diesel spray and propagates into the space in the direction perpendicular to the diesel spray envelope. The algorithm incorporates geometrical information of all spatial constraints and it can provide a universal solution for various piston or cylinder head designs. The diesel and NG combustion models run concurrently to arrive at a complete prediction of the heat release history of both fuels, based on detailed information about the evolution of diesel spray, ignition and flame propagation of NG-air mixture.